Split application of inorganic fertilizers in potato (Solanum tuberosum L.)-hybrid maize (Zea mays L.) Intercropping system - Islam, MN; Akhteruzzaman, M; Alom, MS (Bangladesh Journal of Agricultural Research, 2013)
The experiment was conducted at the research field of Agronomy Division, BARI, Joydebpur, Gazipur during the rabi season of 2009-10 and 2010-11 to find out economic fertilizer dose along with time of split application of fertilizers to potato-hybrid maize intercropping system for higher productivity. Six treatment combinations were derived through combining two fertilizer doses F1= 255-55-140-40-6-2 and F2=320-73-170-50-6-2 kg/ha NPKSZnB and three levels of split applications viz., S1= 1/3 N and full of PKSZnB (basal as broadcast) + 1/3 N top dressed at 30 DAP (days after planting) of potato + 1/3 N top dressed after potato harvest, S2= 1/3 N & ½ of PKSZnB (basal in potato rows) + ½ of PKSZnB (basal for maize) + 1/3 N top dressed at 30 DAP of potato + 1/3 N top dressed after potato harvest and S3= ¼ N & ½ of PKSZnB (basal in potato rows) + ½ of PKSZnB (basal for maize) + ¼ N top dressed at 30 DAP of potato + ¼ N top dressed at 60 DAP of potato to maize rows only + ¼ N top dressed after potato harvest. Sole crops of hybrid maize and potato with recommended fertilizer dose of 255-55-140-40-6-2 and 135-30-135-15-4-0.5 kg/ha NPKSZnB were included for comparison. The highest tuber yield of potato (24.24 t/ha) and grain yield of maize (9.48 t/ha) were obtained from respective sole crops with recommended fertilizer management. The highest potato equivalent yield (30.26 t/ha), gross return (Tk. 363120/ha), gross margin (Tk. 258620/ha), and benefit cost ratio (3.47) were obtained from F1S3. The results revealed that fertilizer dose of 255-55-140-40-6-2 kg/ha NPKSZnB along with its split application, ¼ N and ½ of PKSZnB (basal in potato rows) + ½ of PKSZnB (basal for maize) + ¼ N top dressed at 30 DAP of potato + ¼ N top dressed at 60 DAP of potato to maize rows only + ¼ N top dressed after potato harvest, might be economically profitable for potato hybrid maize intercropping system. DOI: http://dx.doi.org/10.3329/bjar.v38i3.16971 Bangladesh J. Agril. Res. 38(3): 447-453, September 2013